2010
DOI: 10.1210/en.2009-1474
|View full text |Cite
|
Sign up to set email alerts
|

A Mouse Model of Androgenetic Alopecia

Abstract: Androgenetic alopecia (AGA), commonly known as male pattern baldness, is a form of hair loss that occurs in both males and females. Although the exact cause of AGA is not known, it is associated with genetic predisposition through traits related to androgen synthesis/metabolism and androgen signaling mediated by the androgen receptor (AR). Current therapies for AGA show limited efficacy and are often associated with undesirable side effects. A major hurdle to developing new therapies for AGA is the lack of sma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
37
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 27 publications
1
37
0
Order By: Relevance
“…Therefore, the predominant action of androgens through ARs suggests the potential involvement of AR expression in hair follicles in the pathogenetic development of alopecia (Inui and Itami, 2001). Animal studies have demonstrated that androgens are responsible for growth delay in new hair follicles, acting through the AR pathway (Crabtree et al, 2010). In the present study, the AGA group displayed increased AR expression in the FP region not observed in normal controls, confirming the role of androgen hypersensitivity in this region.…”
Section: Discussionsupporting
confidence: 79%
“…Therefore, the predominant action of androgens through ARs suggests the potential involvement of AR expression in hair follicles in the pathogenetic development of alopecia (Inui and Itami, 2001). Animal studies have demonstrated that androgens are responsible for growth delay in new hair follicles, acting through the AR pathway (Crabtree et al, 2010). In the present study, the AGA group displayed increased AR expression in the FP region not observed in normal controls, confirming the role of androgen hypersensitivity in this region.…”
Section: Discussionsupporting
confidence: 79%
“…This enzyme was reported to be localized in the ORS and in the epidermis (Bayne et al, 1999). In addition, ORS-specific androgen receptor transgenic mice have been reported to mimic androgenetic alopecia characterized by delayed hair regeneration (Crabtree et al, 2010), suggesting that ORS and epidermis potentially play important roles in the androgen synthesis and/or action well-associated with hair growth. Thus, we examined the correlation between the hair density and the StAR expression levels in this study.…”
Section: Discussionmentioning
confidence: 99%
“…However, the efficacy disappears within a few months after stopping therapy and side effects are reported to cause allergic dermatitis and mild scalp irritation. Use of two drugs is limited by low efficacy and unfavorable effect [7]. Therefore, the interest and importance to develop novel preventive and/or therapeutic materials for hair loss have increased recently.…”
Section: Introductionmentioning
confidence: 99%